Proving Cayley Transform operator is unitary

Tags: cayley, operator, proving, transform, unitary
 P: 19 Hi, Was wondering if anyone could give me a hand. I need to prove that the Cayley Transform operator given by U=(A-i)(A+i)^-1 is UNITARY, ie that UU*=U*U=I where U* is the adjoint of U (I am given also that A=A* in the set of bounded operators over a Hilbert space H). My solution so far, is this correct? U=(A-i)(A+i)^-1 so (U)(x) = (A-i)((A+i)^-1)x (U acting on an x) Then (Ux,y)= {INTEGRAL}(A-i)((A+i)^-1)x y(conjugate) dx (1) = {INTEGRAL}x(A-i)((A+i)^-1)(both conjugate)y(all three conjugate) dx (2) =(x,U*y) and so deduce (U*)(y) = (A+i)((A-i)^-1)y and so the adjoint of U is U*=(A+i)(A-i)^-1 It can then be checked that UU*=U*U=I As you can see my main query is the mechanism of finding the adjoint of U for the given U. For clarity in step (1) it is just the y which is conjugated, and in step (2) it is (A-i)(A+i)^-1 which is conjugated and then also the whole of (A-I)((A+i)^-1)y which is also conjugated. Sorry if my notation is confusing, if unsure just ask. Thanks for your help in advance!
HW Helper
P: 6,189

 Quote by Ad123q Hi, Was wondering if anyone could give me a hand. I need to prove that the Cayley Transform operator given by U=(A-i)(A+i)^-1 is UNITARY, ie that UU*=U*U=I where U* is the adjoint of U (I am given also that A=A* in the set of bounded operators over a Hilbert space H). My solution so far, is this correct? U=(A-i)(A+i)^-1 so (U)(x) = (A-i)((A+i)^-1)x (U acting on an x) Then (Ux,y)= {INTEGRAL}(A-i)((A+i)^-1)x y(conjugate) dx (1) = {INTEGRAL}x(A-i)((A+i)^-1)(both conjugate)y(all three conjugate) dx (2) =(x,U*y) and so deduce (U*)(y) = (A+i)((A-i)^-1)y and so the adjoint of U is U*=(A+i)(A-i)^-1 It can then be checked that UU*=U*U=I
How do you conclude this from your expression for U*?

Btw, instead of using the integral, can't you simply use the properties of the adjoint operator?
That is, $(AB)^*=B^*A^*$ and $(A^{-1})^*=(A^*)^{-1}$?

 Quote by Ad123q As you can see my main query is the mechanism of finding the adjoint of U for the given U. For clarity in step (1) it is just the y which is conjugated, and in step (2) it is (A-i)(A+i)^-1 which is conjugated and then also the whole of (A-I)((A+i)^-1)y which is also conjugated. Sorry if my notation is confusing, if unsure just ask. Thanks for your help in advance!
 P: 120 [(A-i)(A+i)-1]* = [(A+i)-1]*(A-i)* = [(A+i)*]-1(A-i)* =(A* - i)-1(A*+i) = (A - i)-1(A+i) Now for instance multiply this with the original operator (A - i)-1(A+i)(A-i)(A+i)-1 Note that A+i and A-i commute hence you get the result. Similiarly for the other way around

 Related Discussions Quantum Physics 2 Differential Equations 1 Calculus & Beyond Homework 1 Quantum Physics 1 Quantum Physics 7